Health promotion for pharmacists - Blenkinsopp, Alison; Panton, Rhona; Anderson, Claire, PhD. (Oxford : Oxford University Press, 2000)
This text encourages involvement of community pharmacists in all aspects of health promotion and discusses the key role of pharmacists in advice on stopping smoking and drugs misuse. It contains clear case studies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pharmacist and patient; Health promotion